ANALISIS STRATEGI MEMBANGUNBRAND IMAGE HALAL TOURISMKECAMATAN SAMBELIA KABUPATEN LOMBOK TIMUR - Muttaqillah Muttaqillah; Zainal Abidin; Lalu Adi Permadi (Master of Management, Mataram University, 2018)
The purpose of this research was to develop marketing communication strategy for building the brand image of halal tourism in Sambelia District of East Lombok Regency. The design used in this research based on qualitative approach. The results of this study indicated that marketing communication strategy already exists in building a brand image of halal tourism in Sambelia District, East Lombok Regency. Marketing communication strategy appropriately in accordance with the internal and external environmentalconditions used to build a brand image of halal tourism in Sambelia District, East Lombok Regency is a Strategy of Development and Communication of Halal Tourism Market and Maintaining Variety of Tourism Attraction in East Lombok, Promotion Strategy with Branding Pesona Halal Lombok Timur and Marketing Communication Strategy with branding of Halal tourism for East Lombok either through internet and tourism exhibition.Keywords:marketing communication strategy, brand image, halal tourism, Sambelia District, East Lombok Regency